-5x+8-3=-7x+2x+3

Simple and best practice solution for -5x+8-3=-7x+2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+8-3=-7x+2x+3 equation:



-5x+8-3=-7x+2x+3
We move all terms to the left:
-5x+8-3-(-7x+2x+3)=0
We add all the numbers together, and all the variables
-5x-(-5x+3)+8-3=0
We add all the numbers together, and all the variables
-5x-(-5x+3)+5=0
We get rid of parentheses
-5x+5x-3+5=0
We add all the numbers together, and all the variables
2!=0
There is no solution for this equation

See similar equations:

| 4x+3(-4x-2)=-94 | | x^2+x-0.6=0 | | 1.7x0.5=6.5 | | 4x+3(-4x-2)=-94 | | 2p+4=-6 | | -5x+12=2x-43 | | 21=11+y | | 4d-7=15 | | 5x-2(7x+3)=75 | | a^2=-80a | | x+2(25-x)=38 | | (x-6)+(3x-6)=36 | | 2+2(x-2)+0.66(x-2)(x-8)=0 | | 1x+(25-x)x2=38 | | ¾x=20 | | 6x(-3)=117 | | 7p+11=46. | | 135=x+146 | | 130=19x-3 | | 2y6•9y4•7y2= | | 5.7f=3 | | 6y+10+2y=2 | | 12x+-18=66 | | 4(i-3)=2i+7 | | 1.8p=7.11 | | |4y+4|-44=-12 | | Y=3.14×d | | 9x+7=25 | | 8(1+5x)+5=-13+27x | | 12=4y=2(y+9) | | 7x-25=10x+5x+23 | | 12=4y=2(y+) |

Equations solver categories